PENGEMBANGAN GAME 2D PLATFORMER HACK AND SLASH GAME “SOUL GENESIS” - Jimmy Christian; Vikky Aprelia Windarni; Surya Tri Atmaja Ramadhani; Dewi Anisa Istiqomah; Fiyas Mahananing Puri (Universitas Amikom Yogyakarta, 2026)
ABSTRACT The development of the gaming industry has led to the emergence of various genres with increasingly diverse gameplay and narrative approaches, one of which is the 2D platformer game with hack and slash elements. This research aims to develop the game Soul Genesis, a 2D hack and slash platformer that combines fast-paced combat mechanics with a storytelling approach based on Javanese folklore. The development method used is the Game Development Life Cycle (GDLC), which includes the stages of initiation, pre-production, production, testing, beta, and release. The game was developed using Unity 2D with the C# programming language and applies a pixel art visual style to support the game's feel. The development results are a functional prototype consisting of several levels with a variety of enemies and challenges. Testing was carried out through alpha testing using the black box method and beta testing involving 30 respondents at the GKM 2024 Expo. The beta testing results showed a user satisfaction level of 82.08%, which is in the